The Effect of The Project-Based Learning Model on Students' Science Process Skills in Physics Learning: A Literature Review - Lutfiatussolihah Lutfiatussolihah; Alia Cahyani (Indonesian Journal of Applied Science and Technology, 2023)
Science process skills are essential competencies in physics learning, yet school development remains suboptimal due to a conceptual mastery focus. Project-Based Learning (PjBL) is believed to overcome this issue. This study aims to analyze and synthesize the influence of the PjBL model on students' science process skills in physics learning. The research method utilizes a qualitative descriptive literature review of 15 scientific articles from the 2014–2023 period obtained from SINTA, Google Scholar, and GARUDA databases. Analysis stages include identification, selection, data extraction, content analysis, and findings synthesis. The review results show that all articles reported a positive PjBL influence on improving students' science process skills across various indicators. PjBL effectiveness is influenced by project implementation quality, material characteristics, media technology support, and learning strategies. In conclusion, PjBL can be an effective alternative learning model to develop science process skills while supporting 21st-century learning implementation.